Zmiany roślinności rezerwatu przyrody Mszar Bogdaniec - Dyderski, Marcin; Jagodziński, Andrzej (Leśne Prace Badawcze, 2016)
Changes of vegetation in forests and wetlands require continuous monitoring and evaluation. Due to the lack of in-depth knowledge, it is still very challenging to predict and record vegetation changes. This study attempts to evaluate changes in forest and transitional bog vegetation over 14 years in the Mszar Bogdaniec nature reserve (West Poland; 21.98 ha). We described the current vegetation using 50 phytosociological relevés conducted in 2012 and 2013. Moreover, we calculated and compared ecological indices describing ecological traits of the vegetation in two different times. We also used Detrended Correspondence Analysis (DCA) to assess changes in floral composition. Most of the studied vegetation traits did not change significantly during the last 14 years. Statistically significant changes occured in the proportion of mosses and cover of the herb layer, both of which increased, as well as species richness in forest plant communities, and the cover of species from Scheuchzerio-Caricetea class in peat bog plant communities, both of which decreased. The current state of the vegetation is a result of former human activity such as drainage and planting monoculture tree stands. The observed changes during the last 14 years were fluctuations rather than direct changes. Encroachment of the woody species into transitional bog is a fluctuation, which may be secondary succession in the long-term.